The pandemic strain of the myrtle rust pathogen, Austropuccinia psidii, hosts multiple mycoviruses - Donald M. Gardiner; Stephen J. Fletcher; Rosalie Sabburg; Andrew D.W. Geering; Grant R. Smith; Madhuja Palaparambil Appukkuttan; Mu Sheen Chang; Thaís R. Boufleur; Chris A. Brosnan; Anne Sawyer (Fungal Biology, 2026)

A Future of Self-Directed Patient Internet Research: Large Language Model-Based Tools Versus Standard Search Engines - Arya Rao; Andrew Mu; Elizabeth Enichen; Dhruva Gupta; Nathan Hall; Erica Koranteng; William Marks; Michael J. Senter-Zapata; David C. Whitehead; Benjamin A. White; Sanjay Saini; Adam B. Landman; et al. (Annals of Biomedical Engineering, 2025)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

The Effect of a Medical Toxicology Inpatient Service in an Academic Tertiary Care Referral Center - Andrew M. King; Shooshan Danagoulian; Michael Lynch; Nathan Menke; Yijia Mu; Melissa Saul; Michael Abesamis; Anthony F. Pizon (Journal of Medical Toxicology, 2019)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)

The influence of curvature on membrane domains - Jeremy Pencer; Andrew Jackson; Norbert Kučerka; Mu-Ping Nieh; John Katsaras (European Biophysics Journal, 2008)

One-carbon metabolism gene polymorphisms and risk of non-Hodgkin lymphoma in Australia - Kyoung-Mu Lee; Qing Lan; Anne Kricker; Mark P. Purdue; Andrew E. Grulich; Claire M. Vajdic; Jennifer Turner; Denise Whitby; Daehee Kang; Stephen Chanock; Nathaniel Rothman; Bruce K. Armstrong (Human Genetics, 2007)